The Usage of Fuzzy MCDM Methods for Empowering Human-Centric Digital Transformation: A Bibliometric Analysis - Onar, Sezi Cevik; Kahraman, Cengiz; Cebi, Selcuk; Oztaysi, Basar (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
In this study, a bibliometric analysis of the use of fuzzy multi-criteria decision-making (MCDM) methods in human-centric digital transformation is conducted. In order to support responsible technological transformation with values like sustainability, transparency, and fairness, a systematic decision-making framework is necessary. The fuzzy MCDM techniques offer effective tools since they are able to deal with uncertainty and human judgement in complex decisionmaking problems. In this study we analyzed the usage areas of these methods in the literature by using Scopus database. The results indicate a growing interest in this field. Fuzzy AHP, TOPSIS, and DEMATEL are the most frequently applied methods, often used with extensions of fuzzy sets. Human centricity and sustainability concepts are often considered together.
Keywords: Fuzzy AHP; Fuzzy TOPSIS; Fuzzy DEMATEL; Fuzzy MCDM; Human Centric; Literature Review; INDUSTRY; Computer Science